Contributions to the palaeofauna of Ptinidae (Coleptera) known from Baltic amber - Bukejs, Andris; Alekseev, Vitalii I.; Cooper, David M.l.; King, Gavin A.; Mckellar, Ryan C. (Zootaxa, 2017)
Hemicoelus favonii sp. nov. is described and illustrated from Eocene Baltic amber. This new fossil species differs from extant congeners in having 11-segmented antennae; a metathoracic ventrite with large impression in its anterior portion; a pronotum distinctly narrower than the elytral base region; the posterior suture of abdominal ventrite 1 weakly arcuate medially; sharp lateral pronotal margins that are incomplete and distinct in their basal half only; elytral striae that are not grouped in pairs; posterior pronotal angles that are rounded; elytral intestriae 3, 5, 7 and 9 that are distinctly convex; and a comparatively small total body size. The presence of Hemicoelus in Baltic amber suggests that moist, rotting wood was available as a microhabitat in the ancient forest. Beyond the new species description, the systematic placement of Anobium jacquelinae Hawkeswood, Makhan & Turner is discussed. A new fossil record for Microbregma waldwico Bukejs & Alekseev, and the first report of the genus Trichodesma LeConte from Eocene Baltic amber are also presented.